Order-to-Disorder and Disorder-to-Order Transitions of Proteins upon Binding to Phospholipid Membranes: Common Ground and Dissimilarities - Reinhard Schweitzer-Stenner (Biomolecules, 2025)
Cytochrome c is one of the most prominent representatives of peripheral membrane proteins. Besides functioning as an electron transfer carrier in the mitochondrial respiratory chain, it can acquire peroxidase capability, promote the self-assembly of α-synuclein, and function as a scavenger of superoxide. An understanding of its function requires knowledge of how the protein interacts with the inner membrane of mitochondria. The first part of this article provides an overview of a variety of experiments that were aimed at exploring the details of cytochrome c binding to anionic lipid liposomes, which serve as a model system for the inner membrane. While cytochrome c binding involves a conformational change from a folded into a partially disordered state, α-synuclein is intrinsically disordered in solution and subjected to a partial coil -> helix transition on membranes. Depending on the solution conditions and the surface density of α-synuclein, the protein facilitates the self-assembly into oligomers and fibrils. As for cytochrome c, results of binding experiments are discussed. In addition, the article analyzes experiments that explored α-synuclein aggregation. Similarities and differences between cytochrome c and α-synuclein binding are highlighted. Finally, the article presents a brief account of the interplay between cytochrome c and α-synuclein and its biological relevance.